Chapter 2.7 RMA Education, Training and Professional Development in North America and Europe - Jeff Ritchie; Emma Lythgoe; John Donovan (Emerald Publishing Limited, 2023)
Starting in the late 1950s with the creation of the National Council of University Research Administrators (NCURA), followed by the formation of other professional organisations both in the USA and Europe, there was a growing sense that research management was indeed a profession. One goal was the creation of professional standards that would lead to a standard training curriculum and, ultimately, a professional credential, and there have been many attempts at developing research administration certification. Now, in the US, accreditation through the Research Administrators Certification Council (RACC) exam has become ubiquitous, whereas in other parts of the world, certification by portfolio is more common. This chapter will compare and contrast the salient features of certification, certificates, and degree programs in research administration and review their development and growth over the past 30 years. The chapter will discuss their relative merits and how they work to advance the profession of research administration.
10.1108/978-1-80382-701-820231016; 10.1108/978-1-80382-701-820231016; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262